SHOULD THE DPD REPUBLIC OF INDONESIA BE PRESERVED? - Hamudy, Moh Ilham A; Rifky, M Saidi (Universitas Muhammadiyah Yogyakarta, 2020)
The DPD never carried-out its task of double-checking the legislation process. DPD membership is also connected with political parties. This study aimed to reexamine the need for the DPD and determine whether the DPD should be preserved or dissolved. This study was limited and focused on the 2004-2019 period and used the literature study and the descriptive method in collecting relevant information. The approach used in this study was a qualitative approach, which was appropriate since the existence of DPD was considered to be multidimensional. The results of the study showed the importance of revitalizing the authority of the DPD. There were a significant gap and inequality of authority between the DPR and the DPD, which was not in line with the bicameral system in other countries. The DPD's affiliation with political parties was very strong, due to multiple interpretations of Law No. 7 of 2017 concerning Elections on the requirements for DPD membership. As such, it is very urgent to optimize the DPD role. The role of the DPD, as a channel for the region's political and economic aspirations and needs in the national policy, should be repositioned according to the demands of the law. Â However, if this role is not achieved, this nation should decide to dissolve the DPD. Of course, it should be conducted through a constitutional mechanism, via amendment of the 1945 Constitution.